2021
DOI: 10.26855/ijfsa.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural By-Product Proteins: Emerging Source for Packaging Applications

Abstract: Regular use of petroleum-based plastic packaging films has led to environmental impact due to their total non-biodegradability. Substantially, the food industry generates waste and agricultural-based raw materials have recently been applied to produce biodegradable, renewable and safe to eat packaging materials as a viable alternative to aforesaid dire consequences. Agro packaging concept has emerged where valuable compounds from by-products such as proteins are extracted from animal or plant sources to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Therefore, they have been studied intensively for their use in the development of edible films and biocomposite materials. These works demonstrated that soy proteins could be successfully transformed into bioplastics with satisfactory mechanical properties by solvent casting, as well as by thermoplastic techniques, such as compression and injection molding. The mechanical properties can be further improved by the addition of other ingredients, such as polysaccharides and lipids. , These soy-based materials, however, are characterized by low water resistance and solubility, which can be further enhanced by acetylation or decreased with cross-linking and post treatments. ,, …”
Section: Upgrading Food Protein Waste Beyond the Food-value Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, they have been studied intensively for their use in the development of edible films and biocomposite materials. These works demonstrated that soy proteins could be successfully transformed into bioplastics with satisfactory mechanical properties by solvent casting, as well as by thermoplastic techniques, such as compression and injection molding. The mechanical properties can be further improved by the addition of other ingredients, such as polysaccharides and lipids. , These soy-based materials, however, are characterized by low water resistance and solubility, which can be further enhanced by acetylation or decreased with cross-linking and post treatments. ,, …”
Section: Upgrading Food Protein Waste Beyond the Food-value Chainmentioning
confidence: 99%
“…The mechanical properties can be further improved by the addition of other ingredients, such as polysaccharides and lipids. 369,446 These soy-based materials, however, are characterized by low water resistance and solubility, which can be further enhanced by acetylation or decreased with cross-linking and post treatments. 369,447,448 Additionally, some studies focused on using byproducts of the soy industry, such as soy whey and okara, and valorized them with minimal pretreatments by producing edible films, functional coating, or films for packaging.…”
Section: Bioplasticsmentioning
confidence: 99%
“…Ultimately it will be a reason to attract a new generation of farmers that have new business concepts to increase the quality level of the local market as well as to capture new export markets. As the third step, giving financial support through lenders to farmers and intermediaries will encourage them to use appropriate packaging materials and refrigerated vehicles and it will be a long-term investment for the industry as well as the country ( Uthpala et al, 2021). Implementing new infrastructures like vehicles that have cold storage facilities, cold storages located at critical DECs will bring more sustainable value addition towards the industry by controlling the natural process of respiration and transpiration of vegetables along the supply chain.…”
Section: Recommendationsmentioning
confidence: 99%